Coconut oil and cholesterol as challenge agents to induce hyperlipidemia and atherosclerosis in hamster animal model - Syarifah-Noratiqah SB; Fairus S; Zulfarina MS; 'Atiqah A; Qodriyah HMS; Isa Naina-Mohamed (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Hyperlipidemia is a condition of high lipid levels in the plasma and often linked with the deposition of lipid droplets in the aorta which initiate the progression of atherosclerosis. Atherosclerosis is a common cardiovascular disorder initiated by the formation of foams cells in the vascular wall which leads to turbulent blood flow, injury to the endothelial layer and subsequent vascular thrombosis. Since the early 1980’s, Golden-Syrian hamsters have been widely used as an animal model in the research of hyperlipidemia and atherosclerosis. The use of hamsters in the hyperlipidemic and atherosclerotic model is due to their lipoprotein profile that is closer to human setting, sensitive to high-fat high-cholesterol (HFHC) diet and a suitable rodent model. Atherosclerosis can be induced in hamsters through dietary challenge with HFHC diet. Over the decades, coconut oil (CNO) was commonly used as the source of fat in the diet design of high saturated fatty acids (SFA) composition. In this review, we summarized published literature with designs involving CNO plus cholesterol-induced hyperlipidemia, atherosclerosis or both. The factors that may influence the ability of CNO and cholesterol combination to induce hyperlipidemia such as the period of dietary intervention, hamster strains and the dietary amount were evaluated and summarized.